THE USING OF ROUNDTABLE TECHNIQUE TO IMPROVE GRADE EIGHT STUDENTS’ ABILITY IN WRITING DESCRIPTIVE TEXT AT SMP SWASTA TAMAN ASUHAN - Pasaribu, Rebekka Viona; Manalu, David Berthony; Efipanias Manihuruk, Leonita Maria (Transpublika Publisher, 2023)
This research aiming to find out whether the use of roundtable technique can significantly improve the grade eight Students’ ability in writing descriptive at SMP Swasta Taman Asuhan. This research used assessment rubric which consisted of 5 aspects: Content, Organization, Vocabulary, Language use and Mechanism. By using quasi-experimental design, the research involved the grade eight students of SMP Swasta Taman Asuhan Pematang Siantar in the academic year 2023/2024 with total of 64 students. In this case, the experimental class was VIII-3 that consisted of 22 students and the control class was VIII-2 that consisted of 22 students. This research used purposive sampling technique. This research used writing test as instrument to collect the data for pre-test and post-test. The result showed that mean score of the experimental class increased from 50.55 to 61.55 after applied the treatment (Roundtable Technique). Mean scores in control class were from 45.85 to 50.55. The T-test computation revealed that there was a significant difference between two classes by used significance 0.05. It was proven that T-test was 1.92 and T-table was 1.68595, which was found that t-value was higher that T-table (1.92>1.68595). Based on the findings, Ha was accepted and Ho was rejected. Therefore, it can be concluded that Roundtable Technique is proven as an effective technique that significantly improves the grade eight students’ ability in writing descriptive at SMP Swasta Taman Asuhan.